2017
DOI: 10.3346/jkms.2017.32.5.858
|View full text |Cite
|
Sign up to set email alerts
|

Early Rehabilitation in Elderly after Arthroplasty versus Internal Fixation for Unstable Intertrochanteric Fractures of Femur: Systematic Review and Meta-Analysis

Abstract: The purpose of this study was to compare the outcomes focusing on the functional outcome and clinical results of replacement arthroplasty (AP) vs. internal fixation (IF) for the treatment of unstable intertrochanteric femoral fracture in elderly. Systematic review and meta-analysis were performed on 10 available clinical studies (2 randomized controlled trials and 8 comparative studies). Subgroup analysis was performed by type of methodological quality. Partial weight bearing time in AP group was earlier than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 26 publications
(64 reference statements)
3
29
1
8
Order By: Relevance
“…Consistent with previous results, [ 19 , 20 ] we also found that PFNA has shorter duration of operation time and less blood loss during surgery than BPH, which implies that PFNA does less surgical injury to patients. However, different from the hypothesis that longer bed-ridden leads to a high rate of general complications, our data incidence of complications 2 weeks after operation in Group A is much lower than Group B.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous results, [ 19 , 20 ] we also found that PFNA has shorter duration of operation time and less blood loss during surgery than BPH, which implies that PFNA does less surgical injury to patients. However, different from the hypothesis that longer bed-ridden leads to a high rate of general complications, our data incidence of complications 2 weeks after operation in Group A is much lower than Group B.…”
Section: Discussionsupporting
confidence: 93%
“…Similar with published data 14 , in this study, we also find that PFNA and BPH have similar functional outcome, which means in the term of functional recovery, either PFNA or BPH is accepted for elderly ITFs patients. Consistent with previous results 17,18 , we also found that PFNA has shorter duration of operation time and less blood loss during surgery than BPH, which implies that PFNA does less surgical injury to patients. However, different from the hypothesis that longer bed-ridden (time of weight bearing after operation in Group A is 47.96 ± 31.16 days longer than 10.68 ± 21.36 days in Group B) leads to a high rate of general complications, our data demonstrated that incidence of bad complications two weeks after operation in Group A is much lower than Group B.…”
Section: Acute Cerebral Infarctionsupporting
confidence: 92%
“…This is consistent with previous reports. 48,49 In contrast to the incidence of general complications after surgery, our results showed that the complications-related operation and rate of reoperation of the AR group are better than that of the IF group. A total of ten articles compared the complications-related operation of the two groups.…”
Section: Postoperative Complications and Reoperationcontrasting
confidence: 57%